Social value for whom, by whom and when? Managing stakeholder dynamics in a UK megaproject. Issue 2 (24th February 2020) - Mulholland, Cara; Chan, Paul W; Canning, Kate; Ejohwomu, Obuks A
Abstract : Studies of project success have generally recognised the role that stakeholder management plays in shaping a collective understanding of value. While these studies have typically focused on new builds, few studies have examined stakeholder management at the end of the life of a built asset. This paper draws on a single megaproject case study into social value in nuclear decommissioning and remediation to examine how 'success' or 'failure' in projects is framed and the implications of stakeholder management in shaping these notions of performance. By tracing the historical development of Dounreay, UK, an experimental nuclear energy site at an advanced stage of decommissioning, it was found that key stakeholders change over time, as those most affected by the changing dynamics of the megaprojects come and go, with resulting impacts on the ways that conditions for success are framed and social value is defined. The authors' findings stress the importance of taking a pluralistic and processual view of stakeholders and demonstrate the need for policymakers, practitioners and researchers to pay greater attention to fragmentation and integration of stakeholders' interests and influences as they change over time. These dynamics of stakeholder management will in turn challenge preconceived ideas of success that are often framed in the early stages of a project.